2020
DOI: 10.3390/ijerph17031048
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Association between European Workers’ Employment Conditions and Employee Well-Being in 2005, 2010 and 2015

Abstract: The aim of this paper is to study whether there is a change in the association between employment conditions and European employees’ well-being at three different time points (the years 2005, 2010 and 2015), characterized by different socio-economic contexts. We based our study on the European Working Conditions Survey. Logistic regressions were performed by adjusting for gender, age, level of education, seniority, occupation, establishment size, activity sector and economic activity. Adjusted odds ratios (ORa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
0
7
0
3
Order By: Relevance
“…Prior research indicates that high levels of employee physical and psychological well-being play a significant role in delivering some important organizational outcomes that are associated with high-performing organizations, such as employee engagement. The proposition that employee well-being is important in developing sustainable levels of employee engagement appears to have sufficient theoretical expectation and empirical research evidence [ 59 ]. Furthermore, He, Morrison [ 60 ] found that employees who reported higher levels of engagement were likely to benefit from a broadened allocation of psychological resources, one of which is employee well-being.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Prior research indicates that high levels of employee physical and psychological well-being play a significant role in delivering some important organizational outcomes that are associated with high-performing organizations, such as employee engagement. The proposition that employee well-being is important in developing sustainable levels of employee engagement appears to have sufficient theoretical expectation and empirical research evidence [ 59 ]. Furthermore, He, Morrison [ 60 ] found that employees who reported higher levels of engagement were likely to benefit from a broadened allocation of psychological resources, one of which is employee well-being.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…The information for the present study was compiled based on a survey applied to a sample, in which the 90,026 registered companies that were distributed in each canton in the province were considered as the population to be investigated; these data are determined by the official statistical body [115]. In this case, for the application of the surveys, we proceeded according to the number of records for each canton, where a higher value of records represents the application of a greater number of surveys, through a proportional allocation, and a random selection in each canton.…”
Section: Sample Datamentioning
confidence: 99%
“…On the other hand, in line with the previous investigations [14][15][16][17][18][19][20], the role of diverse High-Performance Work Practices (HPWP) is studied in another body of work, for example, job design [21] or talent management [22] and their connection with the enhancement of social responsibility or the environmental performance of local governments [23,24], worklife balance [25], or employee well-being [26].…”
Section: Introductionmentioning
confidence: 89%
“…In this paper, we analyze the EU-27 data from the 6th European Working Conditions Survey (EWCS) conducted by the European Foundation for the Improvement of Living and Working Conditions in 2015 [105]. The aim of the EWCS is to provide an overview of the state of labor conditions in the European Union (EU) in order to identify major issues and changes affecting the workplace and contribute to better monitoring the quality of work and employment in Europe [16]. The EWCS questionnaire includes more than 100 items addressing a wide range of issues related to employment conditions and related variables.…”
Section: Participants and Proceduresmentioning
confidence: 99%